Influence of Chemical Treatment on the Physical and Mechanical Properties of Bamboo Fibers as Potential Reinforcement for Polymer Composites - Abhijit Kudva; Mahesha G T; Dayananda Pai (Journal of Natural Fibers)
The growing concern for environmentally friendly biomaterials has spurred interest in natural fibers as a viable alternative to synthetic fibers in various industrial applications. Chemical treatment of natural fibers is necessary in cases where it is desired to enhance their properties and make them more suitable for various industrial applications. These treatments can remove impurities, increase fiber roughness for better adhesion, and modify surface chemistry, ultimately improving characteristics like tensile strength, thermal stability, and compatibility with matrix materials in composites. In this study, chemical treatments, including Sodium Hydroxide, Ammonium Hydroxide, and Potassium Permanganate, were applied to the Bamboo fibers to modify the fiber structure. The tensile strength, morphological characteristics, and degree of crystallinity of the treated fibers were examined. Results revealed that 5% Sodium Hydroxide treatment for 2 hours significantly improved tensile strength and crystallinity compared to other treatments. Chemical composition analysis, XRD, and FTIR analyses confirmed the removal of impurities and amorphous substances. Density measurements indicated a reduction in volume due to the elimination of low molecular weight impurities, leading to increased fiber density. This research provides valuable insights for the development of sustainable biomaterials in the construction and automotive industries such as wall panels, dashboards and door panels.